EFFECTIVENESS OF PROPOSING SOCIAL ASSISTANCE THROUGH THE SIKS-NG APPLICATION IN IMPROVING THE WELFARE OF RURAL COMMUNITIES - Akhsanur Rizqi, Muhammad Aqil; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study analyzes the effectiveness of social assistance applications through the SIKS-NG application in improving community welfare in Ganggang-Panjang Village, Tanggulangin District, Sidoarjo Regency. The main focus is to explore how technology impacts the distribution of social assistance, accelerates access for those in need, and identifies factors that influence successful implementation at the village level. Method: The method used is a qualitative approach with descriptive analysis. The study adapted Richard M. Steers' effectiveness theory, which includes three main indicators: adaptation, goal achievement, and integration. Data was collected through in-depth interviews, participatory observations, and analysis of related documents to get an overview of the implementation of the SIKS-NG application in the field. The findings of this analysis will be compared with the theory of effectiveness to understand the extent to which this application can fulfill the objective of distributing social assistance in villages. Results: The results of the study show that although the SIKS-NG application facilitates the process of proposing social assistance, several challenges still hinder its effectiveness, such as discrepancies in the data of aid recipients, lack of training for operators, and discrepancies in the proposal procedures in the field. Novelty: This study makes a new contribution to analyzing the application of the SIKS-NG application in the context of village governance in Indonesia, especially regarding the challenges of implementing technology at the village level.